Mobile Technology for Primary Stroke Prevention: A Proof-of-Concept Pilot Randomized Controlled Trial. Issue 1 (January 2019) - Krishnamurthi, Rita; Hale, Leigh; Barker-Collo, Suzanne; Theadom, Alice; Bhattacharjee, Rohit; George, Ann; Arroll, Bruce; Ranta, Annamarie; Waters, Debra; Wilson, Denise; Sandiford, Peter; Gall, Seana; et al.
Abstract : Background and Purpose—: Feasibility of utilizing the Stroke Riskometer App (App) to improve stroke awareness and modify stroke risk behaviors was assessed to inform a full randomized controlled trial. Methods—: A parallel, open-label, 2-arm prospective, proof-of-concept pilot randomized controlled trial. Participants were randomized to usual care/control or App intervention group and assessed at baseline, 3, and 6 months. The App measures stroke risk and provides information on management of risk factors. Participants were aged >19 years with at least 2 modifiable stroke risk factors identified, no prior stroke, and owned a smartphone. Results—: Fifty participants (24 control, 26 App) were recruited from 148 eligible participants. Retention in the trial was 87%. Mean cardiovascular health (Life's Simple 7) improved by 0.36 (95% CI, −2.10 to 1.38) in the App group compared with 0.01 (95% CI, −1.34 to 1.32) in controls ( P =0.6733). Conclusions—: These findings support a full randomized controlled trial to test the effectiveness of the Stroke Riskometer for primary stroke prevention. Clinical Trial Registration—: URL:www.anzctr.org.au . Unique Identifier: ACTRN12616000376448.